Evaluation of the Effect of Nanoparticle Presence in Furnace Off-Gas on Heat and Mass Transfer in Extraction Ducting - Johannes Conradie; Andrei Kolesnikov; Kasturie Premlall; Luther Els (Proceedings)
Ferromanganese smelters generate significant amounts of fumes containing saturated vapours of metals [...]